Teaching Social Dilemma through Simulating Cooperation: A Classroom Experiment - Kim, Jae-woo; Hanneman, Robert (Journal of University Teaching and Learning Practice, 2023)
Despite an increased number of case studies simulating social problems in the classroom, due attention has been rarely paid to social dilemma games in light of teaching the key concepts of sociology. We propose a paper-and-pencil experiment designed for sizeable students to simultaneously explore various conditions of sustainable cooperation in a Prisoner’s Dilemma game, with five steps of in-class activities presented in details. We evaluate experimental results quantitatively and the usefulness of game-based learning on the basis of debriefing interviews. Beside positive effects of repeated dyadic interaction and direct communications on cooperation, it is shown that sharing a common goal with group members in the presence of intergroup competition tends to strengthen reputation-based indirect reciprocity. Students seem to learn more deeply and see wider relevance as a product of engaging in the experiment, generating findings from the simulated data, and associating them with real-world examples of reciprocity. Our case study on teaching social dilemma through a simple but novel classroom experiment may provide valuable information to educators and practitioners interested in the effective use of economic games as an interactive teaching method for undergraduates in the setting of higher education.